Pengaruh Penerapan Good Corporate Governance Return On Asset Dan Ukuran Perusahaan Terhadap Nilai Perusahaan(Studi Longitudinal Pada Perusahaan Asuransi Syariah Yang Terdaftar Di Bursa Efek Indonesia) - Threy Wahyu, Agung; Adetio Setiawan, Romi; Hariyadi, Rizky (ILTIZAM Journal of Shariah Economics Research, 2025)
ABSTRACT This study aims to examine and substantiate, through empirical evaluation, the ramifications of Good Corporate Governance (GCG) enactment, Return on Assets (ROA), and organizational magnitude upon the valuation of enterprises within the Islamic insurance domain. The investigatory locus encompasses sharia-compliant insurers—comprising general takaful entities, re-takaful institutions, and wholly sharia-oriented corporations—authorized under the auspices of the Financial Services Authority (OJK). Conceptually, GCG is construed as an integrated managerial framework purposed to augment stakeholder equity, pivoting upon two cardinal doctrines: (1) the prerogative of proprietors to access lucid and verifiable disclosures, and (2) the corporate imperative to furnish accurate, timely, and transparent reporting. Methodologically, this study adopts a quantitative paradigm employing multiple linear regression analysis via the SPSS v26 analytical suite. The investigational cohort was delineated through a purposive sampling strategy, sourced from a census of 32 OJK-registered sharia insurance institutions listed on the official portals of the OJK and the Indonesia Stock Exchange, culminating in a representative subset of four firms. Empirical outcomes elucidate that GCG implementation exerts a statistically significant inverse influence on enterprise valuation. Conversely, ROA manifests a positive and significant association with firm worth, while organizational scale reveals a significant negative correlation. In light of these deductions, it is posited that sharia insurance operators ought to fortify their corporate valuation by advancing GCG enactment synergistically with optimized ROA performance, while strategically calibrating institutional size for value maximization. Keywords: Good Corporate Governance, Return On Assets, Company Size and Company Value